2018
DOI: 10.1634/theoncologist.2018-0143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Molecular Analyses of Esophageal Squamous Cell Carcinoma, Esophageal Adenocarcinoma, and Gastric Adenocarcinoma

Abstract: This study highlights the genomic heterogeneity of gastroesophageal cancers, showing striking molecular differences between tumors originating from different locations. Moreover, this study showed that esophageal squamous cell carcinomas exhibit a unique molecular profile, whereas gastric adenocarcinomas and esophageal adenocarcinomas have some similarities, supporting the fact that adenocarcinomas and squamous cell carcinomas are completely different diseases, irrespective of the tumor location. This raises t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 43 publications
4
135
0
1
Order By: Relevance
“…The literature search identified globally 158 unduplicated articles, 126 of which were excluded after reviewing their title/abstract, which left 32 articles eligible for full text review. After applying our inclusion and exclusion criteria, 18 articles (for 17 cohorts) were selected for this systematic review [7,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] (supplementary Figure S1, available at Annals of Oncology online).…”
Section: Relationships Among Msi Pd-1/pd-l1 Expression and Tmb In Camentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search identified globally 158 unduplicated articles, 126 of which were excluded after reviewing their title/abstract, which left 32 articles eligible for full text review. After applying our inclusion and exclusion criteria, 18 articles (for 17 cohorts) were selected for this systematic review [7,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] (supplementary Figure S1, available at Annals of Oncology online).…”
Section: Relationships Among Msi Pd-1/pd-l1 Expression and Tmb In Camentioning
confidence: 99%
“…The vast majority of the cohorts reported data on patients from the USA, followed by Asian and European subjects. The majority of the manuscripts (59%) investigated original cohorts of patients [7,61,[63][64][65][66][67][68][69][70]75], whereas data derived from external (public or private) databases were used in some papers [59,62,[71][72][73][74].…”
Section: Relationships Among Msi Pd-1/pd-l1 Expression and Tmb In Camentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the present study demonstrated that Rap1A promoted tumor metastasis, possibly via AKT signaling, integrin-mediated adhesion (27,36), MMP9 and EMT; furthermore, the growth-promoting effects of Rap1A in ESCC were associated with tumor heterogeneity, which required further research to elucidate the underlying mechanism. Considering the known amplification of the K-Ras gene in human esophageal cancer (31,32,37), the expression of Rap1A may be an ESCC marker, and inhibitors of Rap1A may be of therapeutic value. In addition, mTOR plays a key role in regulating several fundamental cellular processes, and its hyperactivation is correlated with a number of human cancers (38).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation into their mechanisms will be helpful in preventing and detecting the disease earlier, with the potential to develop new therapeutic targets. 7 …”
Section: Introductionmentioning
confidence: 99%